Clinical profile of ST-elevation myocardial infarction thrombolysed with tenecteplase in Coronavirus Disease 2019 Pandemic: A comparative study - Kamal Kant Jena; G Manohar; C Elamaran; A Rudrappa (Journal of Clinical and Preventive Cardiology, 2021)
Background: Coronavirus disease-2019 (COVID-19) pandemic has affected millions worldwide. The various complications of COVID-19 have been discussed in the recent studies. We would like to discuss about one such cardiovascular complication, ST elevation myocardial infarction (STEMI) in COVID-19, and its characteristics in this article. Methodology: An observational study was done from April 1, 2020, to July 15, 2020, selecting all STEMI patients admitted to a tertiary care center in Chennai and treated with tenecteplase were grouped in to COVID-19 positive and negative. Their presenting features and complications and outcome were studied. Results: A total of 300 patients were admitted with STEMI during the study period, of which 11.66% were COVID-19 positive. Atherosclerotic cardiovascular risk factors were much lower in COVID-19-positive STEMI patients when compared to non-COVID STEMI patients. Mean oxygen saturation at time of presentation in COVID-19 positive and negative patients was 85.1% and 97.5%, respectively (P < 0.001). COVID-19 group had significantly higher noncardiac complications than non-COVID patients (P < 0.001). The average duration of hospital stay in COVID-19 STEMI was 13.6 days, whereas in non-COVID group was 6.8 days (P < 0.001). Higher mortality was found in the COVID-19 positive group (14.28%) when compared to non-COVID STEMI (7.9%; P < 0.001). Conclusion: COVID-19 itself is a systemic inflammatory disease, which could increase the risk of coronary plaque rupture. Thrombosis has also been described as a mechanism underlying certain cases causing presentation of STEMI, because of endothelial dysfunction and hypercoagulable state.